Inner-worldly and other-worldly outreach: organizational repertoires of protestant mission agencies - Bok, Jared (Journal of management, spirituality & religion, 2020)
Over the last few decades, an increasing number of American Protestant mission agencies have been engaging in evangelism and humanitarian activities. What explains this growth and what are its future implications? Applying theories of organizational ecology and religious identity, I examine intra- and inter-organizational factors influencing rates of engagement in the Evangelism and Relief & Development sectors. The study finds that ecological theories, especially of density dependence, that have more commonly been used to study secular organizational foundings and deaths prove compelling in explaining mission agencies' transnational behaviors. Second, contrary to some common assumptions, Evangelical agencies are no different than Mainline Protestant agencies in expanding their activism to include evangelistic or humanitarian activism, suggesting that despite their theological differences, agencies that are commonly dedicated to transnationalism have more that unites than divides them. I conclude by reflecting on what these patterns imply about continued growth prospects in each sector.